STRATEGI PENGEMBANGAN RESTORAN HALAL SEBAGAI PENUNJANG HOTEL SYARIAH (STUDI KASUS DI UNIDA GONTOR INN, UNIVERSITAS DARUSSALAM GONTOR PONOROGO) - Nurmaydha, Agensy; Mustaniroh, Siti Asmaul; -, Sucipto (Dinar Jurnal Ekonomi dan Keuangan Islam, 2018)
Sharia tourism is a new trend of tourism in the world. Sharia tourism opportunities are potentially very profitable. Sharia tourism accommodates many industries, such as halal food, halal travel, halal restaurants, and sharia hotels. One aspect that must be met in the certification of sharia hotels is halal certified restaurants. UNIDA Gontor Inn is one of the hotels in Ponorogo owned by Universitas Darussalam (UNIDA) Gontor which is prepared to be a sharia hotel.The purpose of this study is to determine the strategy of developing hotel restaurants to become halal restaurants as supporting sharia hotels. Determination of the development strategy using the Analytical Hierarchy Process (AHP) method. AHP calculation obtained the highest level factor level priority results, production system 0.454, the highest level goal priority is halal restaurant certificate 0.412, the priority level alternative strategy is the highest weight, determination of the production quality standard of 0.316. Hotel management must focus on determining production quality standards related to input, process and output, including purchasing raw materials, receiving, selecting, storing, processing and serving according to the Halal Assurance System (HAS) so that it can support halal restaurant certification to support the hotel sharia, as well as being a pilot of sharia hotels in Ponorogo.